PROJECT BASED LEARNING METHOD: TEACHING AND LEARNING BAHASA IN D-CLASS OF 2021 NURSING STUDY PROGRAM AT UNIVERSITAS BINA SEHAT PPNI MOJOKERTO - Moh Zainudin; Eka Nurjanah (Institut Pendidikan Tapanuli Selatan, 2023)
The application of project-based learning in the Indonesian Class D Class 2021 Study Program Nursing at Universitas Bina Sehat PPNI Mojokerto is described in this study. Project assignments focus on creating community service initiatives and gathering research based on the outcomes of service projects completed by students at their schools. The project organizes volunteer work for the community and gathers academic papers to help students develop their four language skills listening, speaking, reading, and writing so they are proficient in using Indonesian both orally and in writing. This study makes use of qualitative research techniques, which provide descriptive information via interviews, observations of people's behavior, or written or spoken statements from participants. Observation and documentation are two data collection methods. Both observation and documentation are methods of data acquisition. The researcher's analysis of the data is as follows: (1) Data compression In this process, the data are chosen based on their level of relevance and relationship to the data group. They are then gathered into one unit and coded. (2) presenting data through gathering pertinent data, and (3) drawing inferences to understand the significance of the sporadic symptoms. Based on the findings and discussion, it can be said that students successfully applied the project-based learning approach to language learning when they planned and carried out community service projects. They were also able to construct coherent and methodical scientific articles on the outcomes of their community service projects.